microRNAs as Potential Biomarkers in Adrenocortical Cancer: Progress and Challenges - Cherradi, Nadia (Frontiers in Endocrinology, 2016)
Adrenocortical carcinoma is a rare malignancy with poor prognosis and limited therapeutic options. Over the last decade, pan-genomic analyses of genetic and epigenetic alterations and genome-wide expression profile studies allowed major advances in the understanding of the molecular genetics of adrenocortical carcinoma. Besides the well-known dysfunctional molecular pathways in adrenocortical tumors such as the IGF2 pathway, the Wnt pathway and TP53, high-throughput technologies enabled a more comprehensive genomic characterization of adrenocortical cancer. Integration of expression profile data with exome sequencing, SNP array analysis, methylation and microRNA profiling led to the identification of subgroups of malignant tumors with distinct molecular alterations and clinical outcomes. MicroRNAs post-transcriptionally silence their target gene expression either by degrading mRNA or by inhibiting translation. Although our knowledge of the contribution of deregulated microRNAs to the pathogenesis of adrenocortical carcinoma is still in its infancy, recent studies support their relevance in gene expression alterations in these tumors. Some microRNAs have been shown to carry potential diagnostic and prognostic values while others may be good candidates for therapeutic interventions. With the emergence of disease-specific blood-borne microRNAs signatures, analyses of small cohorts of patients with adrenocortical carcinoma suggest that circulating microRNAs represent promising non-invasive biomarkers of malignancy or recurrence. However, some technical challenges still remain, and most of the microRNAs reported in the literature have not yet been validated in sufficiently powered and longitudinal studies. In this review, we discuss the current knowledge regarding the deregulation of tumor-associated and circulating microRNAs in adrenocortical carcinoma patients, while emphasizing their potential significance in adrenocortical carcinoma pathogenic pathways, in light of recent insights into the role of microRNAs in shaping the tumor microenvironment.